Posttraumatic growth related to the COVID‐19 pandemic among individuals with lived experience of psychiatric disorder. Issue 6 (2nd November 2022) - Lewis, Catrin; Lewis, Katie; Edwards, Bethan; Evison, Claudia; John, Ann; Pearce, Holly; Raisanen, Lawrence; Richards, Natalie; Roberts, Alice; Jones, Ian; Bisson, Jonathan I.
Abstract: Although the COVID‐19 pandemic has been shown to be detrimental to mental health, it may hold a parallel potential for positive change. Little is known about posttraumatic growth (PTG) as a potential outcome for individuals with lived experience of psychiatric disorders following trauma exposure, especially in the context of the COVID‐19 pandemic. Participants were 1, 424 adults with lived experience of a psychiatric disorder who took part in a longitudinal study of mental health during the COVID‐19 pandemic conducted by the National Centre for Mental Health. PTG was measured using the Posttraumatic Growth Inventory–Short Form (PTGI‐SF). Factors hypothesized to be associated with PTG were investigated using linear regression. The mean participant PTGI score was 12.64 ( SD = 11.01). On average, participants reported the highest scores on items related to appreciation of life and lowest on those related to spiritual change subscale. We found the strongest evidence of associations between higher levels of PTG and higher scores on assessment items related to perceived social support, B = 2.86; perceptions of the pandemic as traumatic, B = 4.89; and higher psychological well‐being, B = 0.40. Taken together, we did not observe evidence of widespread PTG related to the COVID‐19 pandemic among individuals with lived experiences of psychiatric disorders.